2023
DOI: 10.1002/cbf.3857
|View full text |Cite
|
Sign up to set email alerts
|

Piper chaba, an Indian spice plant extract, inhibits cell cycle G1/S phase transition and induces intrinsic apoptotic pathway in luminal breast cancer cells

Kumari Sunita Prajapati,
Shashank Kumar

Abstract: Piper chaba (Piperaceae) is a medicinal spice plant that possesses several pharmacological activities. In the present study, we for the first time studied the effect of P. chaba extract on breast cancer cells. P. chaba stem methanolic (PCSM) extract produced time and dose dependent cytotoxicity in luminal breast cancer cells (MCF‐7 and T47D) with a minimal toxicity in breast normal cells (MCF‐10A) at 10–100 µg/mL concentration. PCSM extract exerts 16.79 and 31.21 µg/mL IC50 for T47D and MCF‐7 cells, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
(82 reference statements)
1
1
0
Order By: Relevance
“…In the present study, we found that KU treatment significantly increased Bax/Bcl2 ratio, cytochrome C, cleavage of Caspase 3, and PARP levels in HCT‐116 cells‐derived colonosphere. Increased Bax/Bcl2 ratio, cytochrome C release, Procaspase 3 activation, and PARP cleavage are characteristic events related to intrinsic apoptotic pathway 36,37 . Our study clearly indicates that KU induces intrinsic apoptotic pathway‐mediated cell death in HCT‐116 cells and the derived colonosphere.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…In the present study, we found that KU treatment significantly increased Bax/Bcl2 ratio, cytochrome C, cleavage of Caspase 3, and PARP levels in HCT‐116 cells‐derived colonosphere. Increased Bax/Bcl2 ratio, cytochrome C release, Procaspase 3 activation, and PARP cleavage are characteristic events related to intrinsic apoptotic pathway 36,37 . Our study clearly indicates that KU induces intrinsic apoptotic pathway‐mediated cell death in HCT‐116 cells and the derived colonosphere.…”
Section: Discussionsupporting
confidence: 51%
“…[30][31][32] Our results also showed that KU Increased Bax/Bcl2 ratio, cytochrome C release, Procaspase 3 activation, and PARP cleavage are characteristic events related to intrinsic apoptotic pathway. 36,37 Our study clearly indicates that KU induces intrinsic apoptotic pathway-mediated cell death in HCT-116 cells and the derived colonosphere. Previously it has been shown that JAK2-STAT3 signaling regulates Bcl2 expression in colon cancer cells and thus regulate intrinsic apoptotic pathway in these cells.…”
Section: Xiong Et Al Reported That Pharmacological Inhibition Of Jak2/mentioning
confidence: 60%